Investigation of Rural Participation in Relocation of Rural Settlements Case Study: Relocated villages in south Kerman province in Iran (مسکن و محیط روستا, 2014)
In most post-disaster reconstruction programs, the policy of relocation of some parts or the whole settlement area is technically considered as a suitable solution for the risk reduction and safety against some phenomena such as earthquake, flood, landslide, etc. Studying different experiences reveals that due to the lack of rules and guidelines on how to intervene in rural settlements and also lack of a comprehensive definition of the concepts of in-situ reconstruction and relocation in intervention policies, ambiguity in the application of these approaches and lack of participation of the rural people in new village reconstruction process is such that the relocated survivors are generally not satisfied with relocation and it has often led to the loss of rural people;#39s self-reliance and their loss of place attachment and in some cases, the constructed units in the new village are left unsettled.